The Roles of Smartphone in Students Learning at a Private High School in Cambodia - Moeung, Phany (PT FORMOSA CENDEKIA GLOBAL, 2024)
The study explores the smartphone's role in hindering and helping high school students learn English at a private school in Cambodia. The study used a questionnaire with items adapted from previous literature to investigate a group of students' perceptions of the effects of smartphones on communication, engagement, performance, and self-efficacy. It also looked into the general impacts of smartphones on students' language learning. Responding to the COVID-19 pandemic, an online link to the questionnaire using Google Forms was electronically shared with 200 students in a population of 515. One hundred forty-six participants completed the questionnaire. Descriptive statistics analyses, such as percentage, mean, and standard deviation, were performed for the study. The results from the investigation showed that smartphones positively impacted students' language learning overall. The researcher also discovered a reported association between smartphone and self-efficacy, communication, engagement, and student academic performance. Therefore, classroom teachers, educators, and policymakers need to continue exploring the potential of smartphones in enhancing language learning experience and outcomes and motivating students as they go through different experiences in English language learning. Based on the student participants' quantitative and narrative responses, the study recommends careful use of smartphones in the classroom and strict measures to reduce negative consequences.